Whole genome resequencing reveals genetic relationships and differences between three types of Hainan local pig breeds - Yan, Jiayu; Chen, Jing; Zhao, Shidao; Chen, Jie; Zhang, Lifan (Frontiers in Veterinary Science, 2025)
IntroductionHainan Island, a landmass separated from the Chinese mainland, is characterized by a tropical monsoon maritime climate with ample sunshine and rainfall. It features low-lying plains along the coast and a central mountainous core. These topographical and ecological conditions in the tropics have shaped the unique genetic characteristics of local pig breeds in Hainan. To date, the similarities and differences in the genetic characteristics of different pig breeds, especially pig breeds from different geographical regions, remain unclear.MethodsWhole genome resequencing were applied to 25 Duntou (DT) pigs from the western, 17 Wuzhishan (WZS) pigs from the central, and 23 Wenchang (WC) pigs from the eastern part of Hainan Island. Among the different pig populations, genetic relationships were assessed through ADMIXTURE analysis, phylogenetic tree construction, and multidimensional scaling analysis. Subsequently, genetic differences were determined by identifying differentially selection regions (DSRs) and the candidate genes within these regions.ResultsAfter quality control, 13,614,302 autosomal single nucleotide polymorphisms (SNPs) were used in the present study. The results revealed that DT and WZS pigs had closer genetic connections, whereas the genetic connection between WC and the other two pig breeds was relatively distant. Moreover, 1,174 selected genes from DSRs were identified between DT and WZS pigs, WZS and WC pigs, and DT and WC pigs, which included a number of important candidates associated with the growth properties of WZS pigs, and farrowing and fat deposition in WC pigs. The identified genes are able to serve as a scientific underpinning for the conservation and diversified utilization of these indigenous pig breeds.DiscussionThis study provides a genome-wide view of the genetic structure of pig breeds from different geographical locations in Hainan. Our data may provide the molecular characteristics for the formation of these pig breeds, thus helping us better understand the origin and genetic differences of local pig breeds in Hainan.